Commercialization and Stem Cell Research: A Review of Emerging Issues - Burningham, Sarah (Mary Ann Liebert, Inc., 2013)
Stem cell researchers face pressure to develop therapies that will reach the clinic within a short period of time. Yet, this pressure may be unrealistic, as bringing stem cell innovations to the clinic will likely require significant time and financial investment. In a variety of biomedical fields, some evidence suggests that commercialization pressures and strategies may negatively impact research. These negative impacts may also be felt in the field of stem cell research, unless the challenges and issues are addressed in the design and implementation of commercialization policies. Further inquiry into the impact of commercialization on the field of stem cell research is required.